O storytelling orientado pelas controvérsias para tratar wicked problems : um exercício sobre as temáticas “mulher, trabalho e empreendedorismo” - Simonato, Nicole (Universidade do Vale do Rio dos Sinos, 2019)
In search of solutions to meet contemporary challenges and to promote collective well-being, design is increasingly geared towards improving the ways of being and doing of individuals, communities, companies, and organizations. Among these solutions are projects that deal with wicked problems, which are projects open to numerous solutions and possibilities and that involve a diversity of social actors. Consequently, the diversity of views and conflicts of interest are characteristical to these projects. However, while most methods and tools do not seem to deal or consider constructively these conflicts and disagreements, in this study we propose the creation and experimentation of a new tool called COS (controversy-oriented storytelling), which emphasizes the plurality of opinions through controversy-oriented storytelling. The aim of this research was to understand how COS could be used to treat wicked problems. Thus, it was divided into three stages - (i) the creation of the COS tool experimentation of the COS tool in a workshop; and, finally, (iii) focus groups, in order to understand the designers' perception regarding the COS. The results suggest that COS (i) triggers different perspectives of reality; (ii) makes historical panoramas sensitive; (iii) initiates new dialogues; (iv) generates provocation; (v) stimulates empathy; (vi) promotes transformation; (vii) produces questioning; (viii) encourages the identification of opportunities; and (ix) helps in the imagination of futures. In this sense, it is a tool with the potential to (i) make the amplitude of a wicked problem sensible; (ii) stimulate controversy; and (iii) to transform the way in which designers deal with these types of problems. COS is a unique tool for dealing with wicked problems for using the diversity of points of view to produce ideas in a critical and reflective way.
Keywords: Storytelling; Controvérsias; Wicked Problems; Design; Storytelling; Controversies; Wicked Problems; Design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial